HUMAN EXPLOITATION IN ARAVIND ADIGA’S NOVEL THE WHITE TIGER - Seftina, Dera; Suhadi, Muhammad Fatih (JOURNAL OF LANGUAGE, 2024)
Aravind Adiga’s The White Tiger explores the stark social disparities between the wealthy and impoverished in India, illustrating how systemic poverty perpetuates marginalization. The protagonist, Balram Halwai, narrates his journey from a lower-caste background to becoming a self-made, successful individual in India. Balram's story is not just one of personal ambition but also of navigating a rigidly stratified society. This study addresses two primary issues: the exploitation Balram endures due to his socioeconomic status; and his strategic actions are to attain freedom from the oppressive forces in his life. Using a library research method, the study integrates secondary sources, including books and articles, to deepen the analysis of the novel. Employing a psychological approach, this study examines the psychological complexities of Balram’s character, supported by theories on character development, data credibility, theoretical triangulation, and reliability. Balram is depicted as an astute yet morally ambiguous character, exhibiting selfishness, cunning, irresponsibility, dishonesty, and a lack of remorse. The analysis reveals how his behaviors and attitudes—such as detachment from others and deviant tendencies—are shaped by his environment. India’s entrenched caste system underpins various social issues in the novel, including poverty, unemployment, corruption in education, inadequate healthcare, exploitation, discrimination, and the persistence of hierarchical master-servant relationships. These factors collectively influence Balram’s psychological development, and shape him into a figure both reflective and critical of the society he navigates.